Brahms in the Schumann Library - Phillips, R (Oxford University Press, 2022)
One of the most important points of connection between the young Johannes Brahms and Robert and Clara Schumann was a shared love of literature and reading. Brahms had developed a passion for the writings of the German Romantics while still in Hamburg, and signed many of his earliest compositions as “the young Kreisler” after E. T. A. Hoffmann’s hapless capellmeister. This investigation considers one fascinating source to shed fresh light on Brahms’s rummaging in the Schumann library in Düsseldorf in 1854: his notebooks of literary quotations, commonly known as the Schatzkästlein, or little treasure chest, of the young Kreisler. The chapter demonstrates the striking extent to which Brahms, in assembling his quotations, set about repurposing some of Robert Schumann’s literary treasures and reflects on the crucially significant role played by literature in the development of Brahms’s own musical sensibility.